Body fat mass assessment in different sports - comparison of two field methods - Srdic, B.; Karaba, D.; Stokic, E.; Polzovic, A. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Anthropometry, esspecially skinfold thickness measurement (SKF), and bioelectrical impedance analysis (BIA) are widely used non-invasive methods of body fat assessment in everyday clinical practice. Different reliability and validity studies gave very variouse results of their comparison. Studying of obese and non-obese subjects also shown dependence of body fat estimation results on nutrition levels. The aim of this study was to show our experiences in application this two methods, by examining their relationship in different groups of athletes. Methods In 151 male athletes (73 basket-ball players, 11 boxers, 28 volley-ball players, 21 rowers and 18 hand-ball players - average age 19.88±4.75 years), body weight, body height and skinfold thickness were measured, body mass index (BMI) was calculated and body fat mass was obtained using bioelectrical impedance analysis (Omron BF 300) (FAT%BIA) and the age- and sex- specific equations (Jackson&Pollock, 1978; Forsyth&Sinning, 1973) (FAT%SKF). Results FAT%BIA values were higher comparing to FAT%SKF in all groups of athletes (14.60±4.81% vs. 7.88±7.33% in basket-ball players, 7.46±3.68 vs. 8.71±3.22 in boxers, 13.60±3.91 vs. 10.64±4.38 in volley-ball players, 14.88±5.00 vs. 12.89±4.69 in rowers and 15.22±4.00 vs. 13.28±4.54 in hand-ball players). All compared values correlated significantly with each other, with exception of group of basket-ball players. Differences between FAT%BIA and FAT%SKF ranged from -24.13% and +3.66% for group of basket-ball players, -4.60% and +8.68% for boxers, -8.50% and +8.88% for volley-ball players, -10.04% and +4.71% for rowers, -10.68% and +2.50% for hand-ball players. Difference between these two methods (FAT%BIA-FAT%SKF) had significantly negative correlation with BMI values in basket-ball (-0.246) and volley-ball players (-0.406). Discussion/Conclusion Results indicate of necessity of caution by using different methods of body fat assessment. In despite of significant correlation between derived data, skinfold thickness method and bioelectrical impedance analysis has shown large individual differences, especially in a group of basket-ball players. The best agreement between gained results was found in a group of boxers. Differences between two methods were also significantly depended on BMI values in groups of basket-ball and volley-ball players, which requests application of more accurate methods.